Structural Changes in the Fallopian Tubes in Patients With Ectopic Pregnancy - G. P. Titova; M. M. Damirov; I. V. Anchabadze; A. A. Medvedev (Неотложная медицинская помощь)
Relevance.Ectopic (extrauterine) pregnancy (EP) occupies a leading place in the structure of urgent gynecological morbidity. This pathology poses a threat to the health and life of a woman, being one of the leading causes of maternal mortality during pregnancy during the first trimester. Among emergency gynecological operations, surgical interventions for EP make up about 50%, and in recent years, most operations have been performed by the laparoscopic method. However, up to now, the pathomorphological changes in the fallopian tubes in patients with EP remain poorly understood.Purpose of the study. To study the features of pathomorphological changes in the fallopian tubes in women with tubal pregnancy, operated on by the laparoscopic method, to substantiate the volume of surgery in patients with this pathology.Material and methods. Morphological examination was performed in 100 women operated on for tubal pregnancy using the laparoscopic method. A comprehensive morphological study of the fallopian tubes removed during the operation was carried out.Results and discussion. The implantation of the ovum in the fallopian tube led to significant changes in its macro- and microstructure, which were caused by the invasion of chorionic villi and involved all layers of the tube wall, differing only in the depth of penetration and prevalence. The anatomical features of the structure of the fallopian tubes contributed to the deep invasion of the ovum into the myosalpinx and subserous parts of the tube, creating the possibility of wall rupture in this area.Conclusions. 1. In all cases of ectopic pregnancy, implantation of the ovum was accompanied by invasion of cytotrophoblast and syncytiotrophoblast, and it involved all layers of the tube wall, differing only in depth and prevalence. The invasive properties of the cytotrophoblast lead to the development of pronounced degenerative changes in the tube wall, which leads to functional inferiority of the tube after the onset of tubal pregnancy in it.2. The chronic productive endomyosalpingitis diagnosed in most patients with ectopic pregnancy with deformation of the tube lumen against the background of changes in the tube wall caused by cytotrophoblastic invasion is an indication for tubectomy. Performing organ-preserving operations on an anatomically and functionally altered fallopian tube is impractical, since it is a high risk factor for recurrent tubal pregnancy in this tube.